Characteristics of Lipid Profile Levels in Ischemic Stroke Patients at Ibnu Sina Hospital 2023 - Sri Wahyu; Arina Fathiyyah Arifin; Mochammad Erwin Rachman; Sri Julyani; Ahmad Naufal Aswan (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Stroke is a clinical sign that develops suddenly due to focal (or global) brain function disorders with symptoms that last for 24 hours or more, and can cause death. This study aims to determine the characteristics of lipid profile levels in ischemic stroke patients at Ibnu Sina Hospital, Makassar, January - June 2023. Method: The research used is a quantitative research type with a descriptive research design, using medical record data from Makassar Hospital which aims to determine the description of lipid profile levels in ischemic stroke patients at Ibnu Sina Hospital Makassar. Result: This study showed that 70 people (58%) of the total sample experienced an increase in total cholesterol levels and 50 people (42%) were within normal limits. 65 people (50%) of the total sample experienced an increase in LDL levels and 65 people (50%) were within normal limits. 82 people (63%) of the total sample experienced a decrease in HDL levels and 48 people (37%) were within normal limits. And 105 people (81%) of the total sample experienced an increase in triglyceride levels and 25 people (19%) were within normal limits. Conclusion: This study concluded that 70 people (58%) of the total sample experienced an increase in total cholesterol levels and 50 people (42%) were within normal limits. 65 people (50%) of the total sample experienced an increase in LDL levels and 65 people (50%) were within normal limits. 82 people (63%) of the total sample experienced a decrease in HDL levels and 48 people (37%) were within normal limits. And 105 people (81%) of the total sample experienced an increase in triglyceride levels and 25 people (19%) were within normal limits.